sep16 - the universal property for free groups, we may dene...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
Math 5125 Friday, September 16 September 16, Ungraded Homework Exercise 6.3.1 on page 220 (first half) Let F 1 and F 2 be free groups of finite rank. Prove that F 1 = F 2 if and only if they have the same rank. Suppose F 1 and F 2 are free groups of the same rank, say F 1 = F ( X ) , F 2 = F ( Y ) , and we have set maps α : X Y and β : Y X such that αβ and βα are the identity on Y and X respectively. Then there exist homomorphisms θ : F ( X ) F ( Y ) such that θ ( x ) = α ( x ) and φ : F ( Y ) F ( X ) such that φ ( y ) = β ( y ) for all x X and y Y . Note that θφ : F ( Y ) F ( Y ) is a homomorphism such that θφ ( y ) = αβ ( y ) = y for all y Y . By uniqueness of homomorphisms, we see that θφ is the identity map on F ( Y ) . Similarly φθ is the identity map on F ( X ) . This proves that F ( X ) = F ( Y ) . We haven’t used the hypothesis of finite rank in this part. Conversely suppose F 1 = F 2 , say F 1 = F ( X ) and F 2 = F ( Y ) where | X | = r and | Y | = s , and that F 1 and F 2 have different rank. Without loss of generality r > s . Also we have an isomorphism θ : F ( Y ) F ( X ) . Write X = { x 1 ,..., x r } and Y = { y 1 ,..., y s } . By using
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: the universal property for free groups, we may dene an epimorphism : F ( X ) Z r 2 by ( x i ) = ( ,..., , 1 , ,..., ) , where the 1 is in the i th position. This yields an epimorphism = : F ( Y ) Z r 2 . Therefore Z r 2 is generated by the s elements ( y i ) . Since Z r 2 is abelian and ( y i ) has order 1 or 2, we deduce that every element of Z r 2 can be written in the form ( ( y 1 )) 1 ... ( ( y s )) s where i = 0 or 1. We conclude that | Z r 2 | 2 s , which contradicts the fact that | Z r 2 | = 2 r , and the proof is complete. Exercise 6.3.2 on page 220 Prove that if | S | > 1, then F ( S ) is nonabelian. Let x , y S be distinct. Then xy 6 = xy , hence F ( S ) is nonabelian....
View Full Document

This note was uploaded on 01/02/2012 for the course MATH 5125 taught by Professor Palinnell during the Fall '07 term at Virginia Tech.

Ask a homework question - tutors are online